2012
DOI: 10.1111/j.1479-828x.2012.01471.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of maternal abdominal subcutaneous fat thickness and body mass index as markers for pregnancy outcomes: A stratified cohort study

Abstract: SFT at 18-22 weeks gestation is better than BMI as a marker for obesity-related pregnancy outcomes. As SFT is considered a surrogate measure for visceral fat, these results suggest that central obesity is a stronger risk factor than general adiposity in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 24 publications
4
60
1
1
Order By: Relevance
“…40 We have shown a correlation between BMI and SFT2, consistent with a previous report. 29 Our research has also demonstrated that there is a wide variation in SFT1 and SFT2 for any given BMI in the overweight/obese categories ( Figure 1). This variation may be due to individual differences in central obesity and suggests that some women may be placed unnecessarily in high risk maternity clinics based on BMI categorisation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…40 We have shown a correlation between BMI and SFT2, consistent with a previous report. 29 Our research has also demonstrated that there is a wide variation in SFT1 and SFT2 for any given BMI in the overweight/obese categories ( Figure 1). This variation may be due to individual differences in central obesity and suggests that some women may be placed unnecessarily in high risk maternity clinics based on BMI categorisation.…”
Section: Discussionmentioning
confidence: 98%
“…The SFT measurements were taken at the cervix placenta view. 29 This was obtained by placing a standard convex array ultrasound transducer, mid-sagittal and superior to the symphysis pubis, measuring in the midline through the linea alba. Landmarks demonstrated on the ultrasound image were the bladder, cervix and uterus, ensuring that the image contained the skin line and that the tissue in the near field was easily distinguishable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Il semble que le taux de cĂ© sarienne augmente lorsque la graisse a une rĂ© partition Ă  prĂ© dominance centrale [25]. Forts de cet argument, certains auteurs proposent de nouveaux outils qui semblent avoir une meilleure association statistique avec la survenue de cĂ© sarienne que l'IMC : la mesure du tour de taille avant 14 SA et la mesure Ă© chographique de la graisse sous-cutanĂ© e abdominale entre 18 et 22 SA [25,26].…”
Section: Discussionunclassified
“…[2][3][4] It is known that pregnancy leads to an adipose tissue accumulation aiming to nutritionally supply the fetus 5 and VAT excess during early pregnancy may increase adverse perinatal outcomes and metabolic risk in later pregnancy. [6][7][8] Nevertheless, obesity effects on pregnancy outcomes may be determined by VAT deposition. Programming of obesity is determined in fetal life, highlighting the need for a better knowledge of the distribution of fat during pregnancy and its determinants.…”
Section: Introductionmentioning
confidence: 98%